ANALISIS EDUPRENEURSHIP MELALUI PEMANFAATAN LIMBAH ORGANIK DAN ANORGANIK SEBAGAI PENJERNIHAN AIR BERBASIS ALAMI - Rauzatur Rahmi; Fakhrurrazi Fakhrurrazi; Yusrizal Hasja; Dian Rafika; Muslimatul Walidah (Jurnal Tunas Bangsa, 2026)
The development of edupreneurship through the utilization of organic and inorganic waste as natural water purification media offers an innovative approach that integrates education, sustainable technology, and economic empowerment. Organic waste such as agricultural residues and plant-based coagulants exhibits a high capacity for adsorbing organic pollutants and heavy metals, while inorganic waste materials such as sand and gravel are effective filtration media for improving water quality. The integration of these two types of waste results in a low-cost, environmentally friendly water purification system that can be easily implemented at the household scale. Through practical learning using a project-based approach, students can be directly involved in research and technology testing activities, thereby fostering critical thinking skills, creativity, and entrepreneurial competencies. Furthermore, transforming waste into products with economic value creates new business opportunities, including the production of filtration media, installation of natural filtration systems, and provision of nature-based water treatment services. The findings indicate that this edupreneurship model enhances scientific literacy, generates environmental innovation, and creates sustainable business opportunities. Overall, the utilization of organic and inorganic waste for natural water purification has the potential to become a strategic solution in 21st-century education by linking green technology, economic independence, and environmental sustainability.